2009
DOI: 10.1186/1471-2407-9-329
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor AP-1 in esophageal squamous cell carcinoma: Alterations in activity and expression during Human Papillomavirus infection

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is a leading cause of cancer-related deaths in Jammu and Kashmir (J&K) region of India. A substantial proportion of esophageal carcinoma is associated with infection of high-risk HPV type 16 and HPV18, the oncogenic expression of which is controlled by host cell transcription factor Activator Protein-1 (AP-1). We, therefore, have investigated the role of DNA binding and expression pattern of AP-1 in esophageal cancer with or without HPV infection.MethodsSeven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Another factor that significantly contributed to elevated risk in cases was consumption of >3 cups of hot salted tea per day. This is in agreement with other studies from same region in esophageal cancer that showed a strong involvement of hot salted tea along with other genetic factors as a risk towards development of esophageal cancer [38]. The local residents of Kashmir valley prepare tea by using baking soda (sodium bicarbonate) and common salt and boil this tea for 2–3 h unless a thick red brown colored extract is obtained before its consumption.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another factor that significantly contributed to elevated risk in cases was consumption of >3 cups of hot salted tea per day. This is in agreement with other studies from same region in esophageal cancer that showed a strong involvement of hot salted tea along with other genetic factors as a risk towards development of esophageal cancer [38]. The local residents of Kashmir valley prepare tea by using baking soda (sodium bicarbonate) and common salt and boil this tea for 2–3 h unless a thick red brown colored extract is obtained before its consumption.…”
Section: Discussionsupporting
confidence: 90%
“…The local residents of Kashmir valley prepare tea by using baking soda (sodium bicarbonate) and common salt and boil this tea for 2–3 h unless a thick red brown colored extract is obtained before its consumption. It has been assumed that the salts might cause thermal injury to esophageal lining [6] and also it has been reported that salted tea is rich in carcinogenic N ‐nitroso compounds containing approximately 3 ppm N ‐methylnitrosourea which promotes high methylating activity [5] and could possibly alter the activity and expression of host‐cell transcription factors [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blots were stripped and reprobed for β-actin levels to confirm equal loading and normalization. The expression levels of SOCS-1 were evaluated densitometrically by using digital image analysis (Image J software version 1.38, NIH USA) on a scale of 0-255 and the averaged pixel values were re-grouped for analysis on an arbitrary scale as strong =>50%; medium = 10-50%; weak = 1-10% and nil/not detectable <1% as described earlier [32] . Loss of SOCS-1 gene expression in tumor tissue was determined by quantitating and comparing it with SOCS-1 expression in normal tissues.…”
Section: Preparation Of Protein Extract and Western Blotting For Socsmentioning
confidence: 99%
“…Thus, summarizing the function of these TFs in the development of EC and the regulatory influence of GSK3b would direct us toward understanding the potential of GSK3b as a molecular target of EC and other cancers. AP-1, a dimeric transcription factor that is comprised of c-Jun and c-Fos, was shown to highly express in EC and was closely associated with the development of EC (Hussain et al 2009;Jimeno et al 2006). c-Jun has been reported to play a critical role in carcinogenesis and cell apoptosis via emigrating from the cytoplasm to the nucleus (Taira et al 2012;Wang et al 2011d).…”
Section: Gsk3b Affects Tumorigenesis Of Ec Through Transcription Factmentioning
confidence: 99%